2015
DOI: 10.1159/000441613
|View full text |Cite
|
Sign up to set email alerts
|

Organization and Chromosomal Distribution of Histone Genes and Transposable<b><i> Rex</i></b> Elements in the Genome of <b><i>Astyanax bockmanni </i></b>(Teleostei, Characiformes)

Abstract: An important feature of eukaryotic organisms is the number of different repetitive DNA sequences in their genome, a feature not observed in prokaryotes. These sequences are considered to be important components for understanding evolutionary mechanisms and the karyotypic differentiation processes. Thus, we aimed to physically map the histone genes and transposable elements of the Rex family in 6 fish populations of Astyanax bockmanni. FISH results using a histone H1 gene probe showed fluorescent clusters in 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Molina Cytogenet Genome Res DOI: 10.1159/000499748 6 Similar to ribosomal genes, the histone multigene family plays a crucial role in the genomes of eukaryotes [Eirín-López et al, 2009]. The position of histone genes in the chromosomes of many fish species has been shown to be evolutionarily more dynamic than previously thought [Pansonato-Alves et al, 2013;Costa et al, 2014;Daniel et al, 2015;Utsunomia et al, 2016], and eventually they were co-located with ribosomal genes [Costa et al, 2016]. In Centropomus , mapping of the H2A-H2B sites revealed a single locus in both studied species in the long arms of the homeologous pair 14, suggesting evolutionary conservatism of this multigene family ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Molina Cytogenet Genome Res DOI: 10.1159/000499748 6 Similar to ribosomal genes, the histone multigene family plays a crucial role in the genomes of eukaryotes [Eirín-López et al, 2009]. The position of histone genes in the chromosomes of many fish species has been shown to be evolutionarily more dynamic than previously thought [Pansonato-Alves et al, 2013;Costa et al, 2014;Daniel et al, 2015;Utsunomia et al, 2016], and eventually they were co-located with ribosomal genes [Costa et al, 2016]. In Centropomus , mapping of the H2A-H2B sites revealed a single locus in both studied species in the long arms of the homeologous pair 14, suggesting evolutionary conservatism of this multigene family ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The physical mapping of Rex elements performed in six natural population of the neotropical fish A. bockmanni evidenced different patterns suggesting that different mechanisms drive the spread of repetitive sequences among the analyzed population [ 39 ]. Rex1 and Rex6 showed small clusters scattered on most chromosomes of the six populations.…”
Section: The Impact Of Rex Retroelements In Teleost Genomes: An Ovmentioning
confidence: 99%
“…This element was also mapped in the heterochromatic blocks of the congeneric species A. fasciatus sampled from the Tietê river [ 40 ]. Interestingly Rex1, Rex3, and Rex6 signals were detected in the acrocentric B chromosome of A. bockmanni specimens sampled from the Alambari river [ 39 ]. In addition, Fantinatti and colleagues [ 43 ] reported the detection of Rex1 and Rex3 signals in the B chromosomes of Astatotilapia latifasciata .…”
Section: The Impact Of Rex Retroelements In Teleost Genomes: An Ovmentioning
confidence: 99%
“…Other studies have already reported the distribution of retrotransposable elements in the chromosomes of species from Astyanax genus (Pansonato-Alves et al 2013;Silva et al 2013Silva et al , 2014Daniel et al 2015) (Table 1). Similar to our data, Rex1 presented a dispersed pattern of distribution in A. paranae (Silva et al 2014).…”
Section: Discussionmentioning
confidence: 94%
“…Given the important roles of retrotransposable elements on fish evolution, their mapping is very important for understanding the genome structure and evolution process in Astyanax (Characiformes, Characidae) genus (Silva et al 2013(Silva et al , 2014Daniel et al 2015;. Astyanax is an interesting group because present high karyotype diversity, including species with 2n = 52, 50, 48, 46 and 36 chromosomes (Tenório et al 2013;Piscor et al 2015;Nishiyama et al 2016;Piscor et al 2016;Parise-Maltempi 2016a, 2016b).…”
Section: Introductionmentioning
confidence: 99%